2022
DOI: 10.3389/fpubh.2022.792946
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Shock, Financial Flexibility, and Hotels' Performance Nexus

Abstract: This study investigates the nexus of coronavirus disease 2019 (COVID-19) shock, financial flexibility (FF), and firm performance (FP) in Taiwan listed hotel firms. Quantile regression (QR) methods were used to analyze the data from Taiwan Stock Exchange listed hotel firms between 2020 Q1 and 2021 Q2. The results evidence that there is an inversed U-shaped linkage between FF and FP for the hotel industry. Additionally, FF has an inverted U-shaped effect on FP for the asset-light hotel firms for all quantiles ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 72 publications
1
4
0
2
Order By: Relevance
“…Lastly, in testing for the effects of the control variable proxied by size and sales growth, the results showed that these variables have significant effects on performance, with a path coefficient value of 0.236 and a p-value of 0.001 <0.05. These findings are consistent with previous empirical research (Ma et al 2015;Mahmood et al 2018;Song et al 2021;Teng et al 2021;Zhang et al 2022). However, the exogenous variables' variability in explaining the endogenous variables' variation is very limited (12.5%).…”
Section: Discussionsupporting
confidence: 93%
“…Lastly, in testing for the effects of the control variable proxied by size and sales growth, the results showed that these variables have significant effects on performance, with a path coefficient value of 0.236 and a p-value of 0.001 <0.05. These findings are consistent with previous empirical research (Ma et al 2015;Mahmood et al 2018;Song et al 2021;Teng et al 2021;Zhang et al 2022). However, the exogenous variables' variability in explaining the endogenous variables' variation is very limited (12.5%).…”
Section: Discussionsupporting
confidence: 93%
“…Financial slack (FS) is a readily available liquidity cushion in the form of excess cash holdings and debt capacity, which provides financing flexibility by mitigating the impact of adverse liquidity shocks, and financial distress and by moderating suboptimal allocative behavior, namely in the form of underinvestment (e.g., Ref. [ 12 ]). 6 Therefore, for precautionary reasons, firms tend to accumulate liquid assets, such as cash and equivalents, as an ‘insurance’ against liquidity shortfalls arising in adverse states of cash flow generation and to avoid asset fire sales, raising externally costly unanticipated funding, or incurring inefficient underinvestment (e.g., Refs.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…[ [8] , [9] , [10] ]), or explores particular performance dimensions of specific segments of the hotel industry, such as listed hotels (e.g., Refs. [ [11] , [12] , [13] , [14] ]). 2 Yet, the development of blueprints to support the design of prospective strategic scenarios requires the availability of a comprehensive and quantitative assessment of the magnitude of the economic, financial, and social impacts of the Covid-19 shock.…”
Section: Introductionmentioning
confidence: 99%
“…Prvo, finansijska kriza 2008. godine, i drugo, finansijska i zdravstvena kriza kao rezultat virusa COVID-19 i pandemije koju je proglasila Svetska zdravstvena organizacija (Đekić et al, 2022, 36). Sektor turizma i ugostiteljstva je najviše pogođen nastankom pandemije (Mandarić et al, 2022;Matejić et al, 2022;Zhang et al, 2022). Usled propisanih mera za sprečavanje i/ili širenje virusa, poslovanje mnogih preduzeća iz ovog sektora je dovedeno u pitanje (Kalenjuk-Pivarski et al, 2021).…”
Section: Uvodunclassified